2020
DOI: 10.3390/brainsci10110769
|View full text |Cite
|
Sign up to set email alerts
|

The Aetiology of Olfactory Dysfunction and Its Relationship to Diet Quality

Abstract: People with olfactory loss may choose foods rich in sugar, salt and fat to compensate their loss—foods that constitute a Western-style diet (WSD). However, olfactory dysfunction has not been consistently linked to any particular type of dietary change. Here we considered whether the aetiology of olfactory dysfunction may affect consumption of a WSD. Two-hundred and twenty-two people with olfactory dysfunction of varying cause, were tested for chemosensory performance and their frequency of consumption of a WSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Changes in diet with olfactory dysfunction have been discussed by several authors [ 29 , 30 , 31 , 32 ] and discussed in detail by Chaaban et al [ 33 ]. The relationship is complex depending on the nature, duration, and aetiology of the olfactory dysfunction [ 29 ] and can lead to the adoption of both healthier diets of better nutritional quality and diets high in sugar, fat, and salt.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in diet with olfactory dysfunction have been discussed by several authors [ 29 , 30 , 31 , 32 ] and discussed in detail by Chaaban et al [ 33 ]. The relationship is complex depending on the nature, duration, and aetiology of the olfactory dysfunction [ 29 ] and can lead to the adoption of both healthier diets of better nutritional quality and diets high in sugar, fat, and salt.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported that participants obtained food-related pleasure by focusing on chemesthesis via the well-functioning sense of touch. In practice, this was achieved via the perception of the food’s texture, especially by adding crunchy elements [ 20 ], and trigeminal stimulation by adding spices to food [ 20 , 44 ]. The increased preference for crunchy food was further reflected in the results concerning preparation methods, since an increased intake of raw food was found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals experiencing chemosensory disorders commonly report changed eating behaviour [ 31 , 45 ], but mixed results have been reported about the association between intake quality and altered chemosensory function. One study showed a change in diet towards a more Western-style diet—high in fast food, sweet, salty, and/or fats—when suffering from olfactory dysfunction [ 44 ]. Other studies have shown a reduced intake of sweet and fatty food [ 46 , 47 ] and in one study also salty food [ 48 ] with a preference towards fruits and vegetables, indicating a shift towards healthier food choices.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Indeed, a recent study from Germany suggested heterogeneity in intake of components of a Western-style diet in a group of 222 subjects with various causes of olfactory dysfunction. 13 Moreover, recent studies have suggested that CSD, particularly in the aging population, may be associated with decreased appetite, altered perception of foods, poorer nutritional intake and diet quality, and decreased immune system function. [14][15][16] Additionally, a previous population-based study assessing CSD and diet in patients with diabetes mellitus suggested an association between lower caloric intake and olfactory dysfunction.…”
Section: Introductionmentioning
confidence: 99%